Assessment of physical activity: an important epidemiological issue - Lilian C. X. Martins; Paulo de Tarso Farinatti (Brazilian Army, 2017)
Introduction: The body of evidence about the benefits of physical activity (PA) on health is massive. There are several distinct subjective and objective methods to evaluate PA levels, which can be a source of bias in self-reported outcomes. Objective: The purpose of the present essay was to review findings from recent research with particular focus on PA assessment, and point out some issues for future research. Conclusion: The variability among evaluation methods compromises comparability between studies. Special attention should be given to self-report instruments that can lead to some sort of bias. Therefore, it is important for proper theoretical basis with respect to the objectives and types of PA, which should be considered before selecting the instrument to be applied in a given population. Views of several review studies were discussed and recommendations were presented. Quantificação de atividade física: uma importante questão epidemiológica Introdução: O corpo de evidências científicas a repeito dos benefícios da atividade física (AF) para a saúde é massivo. Existem vários métodos subjetivos e objetivos distintos para avaliar os níveis de AF, e desfechos autorrelatados pode ser fonte de viés. Objetivo: O objetivo do presente ensaio foi revisar os achados de pesquisa recente com foco particular na avaliação de PA e apontar algumas questões para pesquisa futura. Conclusão: A variabilidade entre os métodos de avaliação prejudica a comparabilidade entre os estudos. Deve-se dar atenção especial aos instrumentos de autorrelato que podem levar a algum tipo de viés. Por isso, é importante, inicialmente, estabelecer a base teórica adequada com relação aos objetivos e aos tipos de AF. Tais considerações devem ter lugar antes de se selecionar o instrumento a ser aplicado em uma determinada população. Neste trabalho, foram examinados vários estudos de revisão e foram apresentadas recomendações.